2019
DOI: 10.3390/fib7010007
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Chemical and Physical Surface Changes of Thermally Conditioned Glass Fibres

Abstract: A number of analytical techniques were applied to investigate changes to the surface of unsized boron-free E-glass fibres after thermal conditioning at temperatures up to 700 °C. Novel systematic studies were carried out to investigate the fundamental strength loss from thermal conditioning. Surface chemical changes studied using X-ray photoelectron spectroscopy (XPS) showed a consistent increase in the surface concentration of calcium with increasing conditioning temperature, although this did not correlate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Unfortunately, similar to the case of composite materials reinforced with glass fibres, composite materials with basalt fibres show a drastic decrease in mechanical properties after the typical thermal recycling process [6][7][8][9]. In a previous work, basalt fibres heat treated at 600 • C for 1 h in air showed a decrease of~75% of the original tensile strength [10].…”
Section: Introductionmentioning
confidence: 94%
“…Unfortunately, similar to the case of composite materials reinforced with glass fibres, composite materials with basalt fibres show a drastic decrease in mechanical properties after the typical thermal recycling process [6][7][8][9]. In a previous work, basalt fibres heat treated at 600 • C for 1 h in air showed a decrease of~75% of the original tensile strength [10].…”
Section: Introductionmentioning
confidence: 94%
“…They also noted an associated TGA measured weight loss from aminosilane sized fibres in the same temperature range and suggested that, since aminosilane is the commonly used coupling agent in PP compatible sizings, the loss in reinforcement effect of the commercial fibres could be due to thermal degradation of the aminosilane functionality. In a similar vein Jenkins et al reported a TGA study of thermal stability of epoxy compatible sizes on glass and basalt fibres [45] and also confirmed the degradation of aminosilane in the 200-300°C temperature range [46]…”
Section: Thermal Analysismentioning
confidence: 71%